The Effect of Citrus lemon Aromatherapy on Emesis Gravidarum Patient - Bunga Tiara Carolin; Siti Syamsiah; Rian Yuniati (Universitas STRADA Indonesia, 2020)
This research aimed to know the effect of citrus lemon aromatherapy on patients with emesis gravidarum. This quasi-experimental research was done through One Group Pretest-Posttest Design. Samples were taken using total sampling which was 30 pregnant mothers in their first trimester experiencing nausea. The measurement tool used in this research was PUQE. The normality test of this research was carried out by using the skewness and kurtosis value in which it resulted in normal distribution so that the statistical test used was Paired T-test. The research found that the average of morning sickness level during the pretest was 9.57 while after the intervention it decreased to 6.40. In addition, the statistical result obtained was p=0.000. It can be concluded that the provision of citrus lemon aromatherapy can affect the patients with emesis gravidarum.